IDENTIFICATION AND PREVALENCE OF GASTROINTESTINAL PARASITIC WORMS IN KING COBRAS IN BALI - Naro, Ayala Lubiana; Suratma, Nyoman Adi; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2024)
The king cobra (Ophiophagus hannah) has an important role in the ecosystem, this snake eats other snakes so it has a role to keep the number of snakes in balance. However, until now parasitic worm infections in wild king cobras in Bali have not been reported, so research is needed to determine the genus of parasitic worms that infect wild king cobras in Bali and their prevalence. This research was conducted on 15 wild king cobras by taking faecal samples which were examined using the floating method, and taking oral samples which were examined directly under a microscope. The test results showed that wild king cobras in Bali can be infected with nematodes of the genus Kalicephalus sp., Strongyloides sp., Capillaria sp., and Rhabdias sp. Any king cobra infected with worms can have a single or mixed infection. The results of the research shows that the type of worm that infects the king cobras in Bali are worms of the genus Kalicephalus sp. (100%), Strongyloides sp. (60%), Capillaria sp. (73.3%), and Rhabdias sp. (6.67%), each king cobra can be infected by 1-4 types of worms, and the oral test of the snake only found Kalicephalus sp. (53.3%). It can be concluded that the types of worms that infect king cobras in Bali are nematodes of the genus Kalicephalus sp., Strongyloides sp., Capillaria sp., and Rhabdias sp. The prevalence of worms that infect king cobras in Bali is Kalicephalus sp. (100%), Strongyloides sp. (60%), Capillaria sp. (73.3%), and Rhabdias sp. (6.67%). On oral examination, Kalicephalus sp. (53.3%). It is recommended for snake keepers or veterinarians who handle snakes to examine snakes for worm infections. In addition, it is necessary to carry out further research regarding the identification and prevalence of gastrointestinal worm parasites and other types of worm parasites.